Health of People, Health of Planet and Our Responsibility Climate Change, Air Pollution and Health - Al-Delaimy, Wael; Ramanathan, Veerabhadran; Sánchez Sorondo, Marcelo (Springer Nature, 2020)
"This open access book not only describes the challenges of climate disruption, but also presents solutions. The challenges described include air pollution, climate change, extreme weather, and related health impacts that range from heat stress, vector-borne diseases, food and water insecurity and chronic diseases to malnutrition and mental well-being. The influence of humans on climate change has been established through extensive published evidence and reports. However, the connections between climate change, the health of the planet and the impact on human health have not received the same level of attention. Therefore, the global focus on the public health impacts of climate change is a relatively recent area of interest. This focus is timely since scientists have concluded that changes in climate have led to new weather extremes such as floods, storms, heat waves, droughts and fires, in turn leading to more than 600,000 deaths and the displacement of nearly 4 billion people in the last 20 years. Previous work on the health impacts of climate change was limited mostly to epidemiologic approaches and outcomes and focused less on multidisciplinary, multi-faceted collaborations between physical scientists, public health researchers and policy makers. Further, there was little attention paid to faith-based and ethical approaches to the problem. The solutions and actions we explore in this book engage diverse sectors of civil society, faith leadership, and political leadership, all oriented by ethics, advocacy, and policy with a special focus on poor and vulnerable populations. The book highlights areas we think will resonate broadly with the public, faith leaders, researchers and students across disciplines including the humanities, and policy makers."